The effect of leadership style and work discipline on the performance of Tangerang City DPRD Secretariat Employess - Solekhah Nur Agustyani; Herayati Herayati; Martinus Wahyu Purnomo (Trigin Publisher, 2023)
Based on the results of temporary observations in the field, it appears that there are several problems related to employee performance. In terms of leadership style and in terms of work discipline. If this is left unchecked and does not get attention, it will have an impact on the performance of the employees of the Tangerang City DPRD Secretariat. This study aims to determine whether leadership style and work discipline simultaneously or partially affect the performance of employees of the Tangerang City DPRD Secretariat. The sample of this research is 39 respondents. The data analysis technique used is the multiple linear regression equation. The results of the study show that Leadership Style and Work Discipline simultaneously influence the Employee Performance of the Tangerang City DPRD Secretariat, with an F count of 214.338 > F table of 3.26 and a sig value of 0.00 <0.05. Leadership style partially has a significant effect on the performance of Tangerang City DPRD Secretariat employees with a t count of 7.355 > t table of 2.02809, with a sig value of 0.000 <0.05 and Work Discipline partially has a significant effect on the performance of Tangerang City DPRD Secretariat Employees with a t value count 5.478 > t table 2.02809, with a sig value of 0.000 <0.05.